2014
DOI: 10.1021/co5001037
|View full text |Cite
|
Sign up to set email alerts
|

Robust Suzuki–Miyaura Cross-Coupling on DNA-Linked Substrates

Abstract: The Suzuki-Miyaura cross-coupling is one of the most widely employed reactions in medicinal chemistry. To apply this reaction to DNA-encoded library technology (ELT), an alternative approach in the discovery of small molecule hits and leads, we explored the Suzuki-Miyaura cross-coupling on DNA-linked aryl halides. Pd(PPh3)4 was demonstrated to be an effective catalyst for cross-coupling with on-DNA halide substrates under aqueous conditions. It efficiently catalyzes the coupling of phenyl halides (iodide or br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
108
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 30 publications
1
108
0
2
Order By: Relevance
“…9,20,3335 Following a test reaction, sensor beads are analyzed as before, and the solution is analyzed by HPLC and MALDI-TOF MS to determine the conversion of 5′-amino oligonucleotide starting material to DNA-conjugated product (Table 2). Condensation of 5′-amino oligonucleotide substrate with Fmoc-Lys(Alloc)-OH in the presence of the activator DMT-MM, a staple amide bond forming reaction in DNA-encoded library synthesis, 20,41 proceeds with 65% yield and 69% DNA remaining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,20,3335 Following a test reaction, sensor beads are analyzed as before, and the solution is analyzed by HPLC and MALDI-TOF MS to determine the conversion of 5′-amino oligonucleotide starting material to DNA-conjugated product (Table 2). Condensation of 5′-amino oligonucleotide substrate with Fmoc-Lys(Alloc)-OH in the presence of the activator DMT-MM, a staple amide bond forming reaction in DNA-encoded library synthesis, 20,41 proceeds with 65% yield and 69% DNA remaining.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent Alloc deprotection 34 yields a mix of Alloc-deprotected (70%) and fully deprotected product (30%), and 50% DNA remaining. Published Suzuki-Miyaura cross-coupling conditions 33 leave 30% of amplifiable DNA remaining. Conventional solution-phase library preparation includes HPLC purification, likely eliminating synthesis products attached to Pd-catalyzed DNA cleavage products (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In general terms, we have found that the usual amount of DNA that we append to the beads 118 will tolerate 3–4 acylations of secondary amines, or 5–6 acylations of primary amines under our standard conditions before the amplifiable level of DNA drops too low to be of use as an encoding tag. Some organometallic reactions, such as Suzuki couplings 119 , also inactivate about 50% of the DNA templates on the bead. Therefore, in the future it will be important to develop new library designs of different types of molecules that can be made with gentler reactions.…”
Section: Dna-encoded Oboc Librariesmentioning
confidence: 99%
“…68 DELs, however, bridge a significant chemotype divide by moving library content away from the space of naturally occurring biopolymers found in display libraries and into the more drug-like space of high-throughput screening (HTS) compound collections. 4,9,10 The plunging costs of both DNA synthesis and next-generation sequencing (NGS) have positioned DEL technology as a promising companion to industrial HTS platforms 11 because it offers access to larger compound collections and lead identification is more economical and expeditious.…”
Section: Introductionmentioning
confidence: 99%